Active power control in a hybrid PV-storage power plant for frequency support. (1st March 2017) - Bullich-Massagué, Eduard; Aragüés-Peñalba, Mònica; Sumper, Andreas; Boix-Aragones, Oriol
Highlights: An active power control for hybrid PV-storage power plant is proposed. Grid code requirements are addressed in the power plant controller. Storage system compensates the solar resource uncertainty. Abstract: The recent increase of intermittent power generation plants connected to the electric power grids may stress the operation of power systems. So, grid codes started considering these power plants should contribute to the grid support functions. Recently, a power ramp rate limitation is being included in several grid codes, which is a challenge for photovoltaic installations due to the lack of inertia. This paper presents a method to deal with the main grid code requirements considering a PV plant with an energy storage device, where a strict two-second time window ramp rate restriction is applied. A direct ramp rate control strategy is used, which includes a dynamic SOC control and battery support functionality for active power setpoint compliance. The control strategy is validated by simulations.